DESENTRASLISASI DAN MONOISME MASYARAKAT (PRAKTEK ELIT LOKAL MELANGGENGKAN DOMINASI) - Firman, Firman (Program Studi Ilmu Pemeritahan Fakultas Ilmu sosial dan Ilmu Politik Universitas 17 Agustu, 2018)
This study on decentralization and the birth of new monoism in the structure of society in South Sulewesi.Praktek domination of power is practiced with the ways of politicization of democracy.Convenience of community monoism as if can not be unstoppable with the existing regulations.Perlu there is a policy and regulation for community monoism practice is not takes place in a massive and beneficial manner only to certain groups. The indication of the management of a region that eludes a group of elites makes the circulation of power increasingly difficult.